PENGARUH PEMBERIAN AROMATERAPI LEMON TERHADAP INTENSITAS EMESIS PADA IBU HAMIL - Pratiwi, Wayan Sasmita; Arimini, Ni Wayan; Dewi, I Gusti Agung Ayu Novya (Fakultas Ilmu Kesehatan, 2025)
HCG (Human Chorionic Ganandotrophin) levels. Emesis gravidarum can cause various impacts on pregnant women, one of which is a decrease in appetite which results in changes in electrolyte balance and changes in body metabolism. This condition can turn into hyperemesis gravidarum if not treated immediately. The aim of this research was to determine the effect of giving lemon aromatherapy on the intensity of emesis in pregnant women. This research used a quasi-experimental design with a pre-test and post-test control group, this research was conducted in two groups. One group was given treatment and another group as control, then observed before (pre-test) and after (post-test). This research was conducted on 56 pregnant women using a technique (consecutive sampling). This study obtained the results of the mean nausea and vomiting intensity score for the treatment group and the control group using the Mann-Whitney Test analysis, namely a p value of 0.000 < 0.05. It can be concluded that there is a difference in the intensity of nausea and vomiting in pregnant women between the treatment group and the control group, and it is proven that lemon aromatherapy can have a significant effect on reducing nausea and vomiting in pregnant women. Researchers suggest that midwives can use lemon aromatherapy as a non-pharmacological alternative to reduce nausea and vomiting in pregnant women